Prognostic significance of pathological response and lymph node status in neoadjuvant immunotherapy for potentially resectable non-small cell lung cancer - Yuan Xu; Dongjie Ma; Yingzhi Qin; Hongsheng Liu (Annals of Medicine)
Objective To evaluate the predictive value of pathological response and lymph node status on progression-free survival (PFS) in patients with potentially resectable non-small cell lung cancer (NSCLC) receiving neoadjuvant immunotherapy.Methods A retrospective analysis was conducted on 143 patients with potentially resectable NSCLC who underwent neoadjuvant immunotherapy followed by surgical resection. Pathological response, lymph node involvement, and clinical outcomes were comprehensively assessed using Kaplan-Meier analysis and Cox regression.Results Both major pathological response (MPR) and complete pathological response (CPR) significantly correlated with improved PFS (p < .01), with no statistically significant difference between them (p = .15). Lymph node involvement adversely affected PFS (p < .01). A novel risk stratification approach based on pathological response and nodal status effectively distinguished prognostic groups, with 3-year PFS rates of 98.9%, 78.9%, and 53.3%. Cox regression identified gender (HR = 0.25, p = .03), pathological response (HR = 6.02, p < .01), and lymph node stage (HR = 2.30, p = .01) as independent PFS predictors.Conclusion In potentially resectable NSCLC, MPR and CPR demonstrate similar PFS benefits after neoadjuvant immunotherapy. Lymph node status significantly influences prognosis, even in initially unresectable cases. The proposed risk stratification provides a valuable tool for personalized management in this challenging patient population.